2019
DOI: 10.1039/c9nr02858g
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the DNA complexation state of pBAE polyplexes in cells with super resolution microscopy

Abstract: The future of gene therapy relies on the development of efficient and safe delivery vectors. Poly(β-amino ester)s are promising cationic polymers capable of condensing oligonucleotides into nanoparticlespolyplexesand deliver them into the cell nucleus, where the gene material would be expressed. The complexation state during the crossing of biological barriers is crucial: polymers should tightly complex DNA before internalization and then release to allow free DNA to reach the nucleus. However, measuring the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Whereas oligonucleotides do not need to translocate into the cell nucleus for gene expression, this is essential for DNA. New developments in optical microscopy recently enabled, for the first time, imaging of the fate of internalized C3Ms with nanometric resolution [ 63 , 83 , 84 ]. This shed light on various aspects of nucleus internalization, although much remains to be elucidated.…”
Section: Biotechnological Applications Of C3msmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas oligonucleotides do not need to translocate into the cell nucleus for gene expression, this is essential for DNA. New developments in optical microscopy recently enabled, for the first time, imaging of the fate of internalized C3Ms with nanometric resolution [ 63 , 83 , 84 ]. This shed light on various aspects of nucleus internalization, although much remains to be elucidated.…”
Section: Biotechnological Applications Of C3msmentioning
confidence: 99%
“…pDNA-based C3Ms must remain intact after endosomal escape, because free pDNA is rapidly digested in the cytosol. Two-color direct stochastic optical reconstruction super-resolution microscopy revealed that pDNA-based C3Ms concentrated in the perinuclear region after cell incubation for approximately 12 h [ 84 ]. Passive translocation of DNA-based C3Ms can be achieved in dividing cells, where the nuclear membrane dissociates during cell mitosis.…”
Section: Biotechnological Applications Of C3msmentioning
confidence: 99%
“…Here, broad-spectrum anticancer drug DOX was used as the model drug, and loaded into the liposome core which was prepared from lipids. The polymer poly(b-amino ester) (PBAE) which has been widely used in drug and/or gene targeted delivery for cancer therapy was selected as pH-responsive layer for drug controlled release (Zhang et al, 2014;Riera et al, 2019). HA, a main component in the extracellular matrix of connective tissue, was selected to form the outside shell of NPs (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[ 58 ] The polymer chains of PbAE are degradable and can be removed from the cells, leading to low cytotoxicity. [ 59 ] When used in mRNA delivery, basic PbAE exhibits a low efficiency in APCs. [ 60 ] However, PbAE modification is able to enhance the interaction of polyplexes with endosomal membranes and promote endosomal escape.…”
Section: Mrna Delivery Platformsmentioning
confidence: 99%